PENGARUH KOMPETENSI, PELATIHAN, DAN PENGALAMAN KERJA TERHADAP KINERJA KARYAWAN DI PT. BINTANG KADIRI KABUPATEN KEDIRI - Amelia, Vicky Media; Jatmiko, Udik; Salim, Helmi Agus (Commodities, Journal of Economic and Business, 2024)
The purpose of this research was to determine the effect of competence, training, and work experience on the employee performance of PT. Bintang Kadiri in Kediri, either simultaneously or partially. The method of analysis used multiple linear regression with a population and sample used as many as 47 people. The sampling technique used saturated sampling. This type of research is quantitative. The results showed that competence, training, and work experience, partially or simultaneously significant effect on employee performance of PT. Bintang Kadiri in Kediri.